Content and process: organizational conflict and decision making - Gaba, Vibha; Joseph, John (Frontiers in Psychology, 2023)
The foundational work in the Carnegie perspective established conflict as endemic to organizations and a driver of organizing behavior and decision making. Organizations as a system of coordinated action among interdependent individuals and groups with different preferences, interests, information, or knowledge create the potential for pervasive and ongoing latent goal conflict. At the same time, extant psychology research has devoted considerable attention to identifying the content and intensity of conflict, focusing on the relationship between different types of conflict and their impact on group outcomes. The Carnegie perspective also assumes that the need for joint decision-making and the differences in goals or perception of reality are never fully resolved. As a result, it has paid attention to the processes through which conflict is addressed - by attending sequentially to goals, decentralizing information, accumulating excess resources, and forming coalitions rather than formal mediating procedures. The assessment of the psychology and organizational theory research also suggests that future work focusing on organizational conflict as latent, situated, and dynamic would enable greater clarity on how organizations make decisions.